2007
DOI: 10.1159/000100044
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Coronary Artery Calcification in Predialysis Patients

Abstract: Background: In patients on dialysis coronary artery calcification (CAC) rapidly proceeds due to impaired mineral metabolism and/or exogenous calcium load. Progression has not been assessed in patients with chronic kidney disease not yet requiring dialysis (CKD patients). In this study, rate and determinants of CAC progression have been evaluated in CKD patients who are exposed to minor derangement of mineral metabolism and calcium load. Methods: Consecutive patients were enrolled. Exclusion criteria were: symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 50 publications
2
52
1
1
Order By: Relevance
“…12 Coronary artery calcification is one of the reasons why hyperphosphatemia, hypercalcemia lead to cardiovascular events and mortality. 5,6,[17][18][19][20] However, after multivariate adjustment, the AHRs for mortality according to different categories of time average mineral values sorted by K/DOQI guidelines demonstrated no survival difference among all mineral values in our study. This conclusion is not similar to previous studies.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…12 Coronary artery calcification is one of the reasons why hyperphosphatemia, hypercalcemia lead to cardiovascular events and mortality. 5,6,[17][18][19][20] However, after multivariate adjustment, the AHRs for mortality according to different categories of time average mineral values sorted by K/DOQI guidelines demonstrated no survival difference among all mineral values in our study. This conclusion is not similar to previous studies.…”
Section: Discussioncontrasting
confidence: 68%
“…[1][2][3][4] Coronary artery calcification might be explanatory. 5,6 Therefore, Kidney Disease Outcomes Quality Initiative (K/DOQI) provides the target ranges of mineral values (Ca, P, PTH). They set target range of serum phosphate, calcium, intact parathyroid hormone and calcium-phosphorus product as 3.5-5.5 mg/dL, 8.4-9.5 mg/dL, 150-300 pg/mL and less than 55, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in healthy adults (53) and CKD patients (54) already observed an association of higher phosphatemia with atherosclerosis and vascular calcification. Russo et al established in a cohort of predialysis patients that higher phosphorus levels were associated with CAC progression (55). Another study performed in CKD patients observed an association between higher phosphorus levels and mortality (56).…”
Section: Discussionmentioning
confidence: 99%
“…The disease progresses rapidly and is associated with fatal and nonfatal cardiovascular events (4,5). It is likely that in CKD patients, who frequently die from coronary heart disease before dialysis initiation, CAC is an important risk factor for cardiovascular events as in patients on dialysis (ESRD patients) (6 -9).…”
mentioning
confidence: 99%